PENGARUH OPINI AUDIT, KOMITE AUDIT, DAN FINANCIAL DISTRESS TERHADAP AUDIT DELAY DENGAN REPUTASI KANTOR AKUNTAN PUBLIK (KAP) SEBAGAI VARIABEL MODERASI - Livia Anggraini, (2022)
This study is a quantitative study that aims to determine the effect of audit opinion, audit committee, and financial distress on audit delay with the reputation of the public accounting firm as a moderating variable. This study uses data from the annual financial statements of the non-primary consumer goods sector listed on the Indonesia Stock Exchange. The selection of sample criteria was carried out using a purposive sampling technique with predetermined criteria and data obtained were 201 samples from 67 non-primary consumer goods sector companies listed on the Indonesia Stock Exchange during the 2018-2020 period. Hypothesis testing in this study uses Moderated Regression Analysis (MRA) with the help of SPSS 26 software and a significance level of 5%. The results of the test show that (1) audit opinion and financial distress have a negative effect on audit delay, (2) audit committee has no significant effect on audit delay, (3) KAP reputation is not able to moderate the effect of audit opinion and audit committee on audit delay, ( 4) KAP reputation is able to moderate the effect of financial distress on audit delay.